Kajian Material Pelapis Tahan Korosi untuk Komponen Molten Salt Reactor dengan FLiBe - Prasetyo Edi Nugroho; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
Molten Salt Reactors (MSRs) are among the most promising Generation IV nuclear reactor technologies due to their high thermal efficiency and inherent safety. However, their long-term operation is significantly challenged by the severe corrosiveness of molten fluoride salts, particularly FLiBe (Li₂BeF₄), which can degrade structural materials under high-temperature conditions. This study aims to compare the corrosion resistance of four candidate coating materials, namely High-Entropy Alloy (HEA), ODS NiMo–Y₂O₃, silicon carbide (SiC), and pyrolytic carbon (PyC), through a comparative literature review approach. The collected data were evaluated based on corrosion rate, surface morphology evolution, and the protective mechanisms developed at temperatures ranging from 650 to 750 °C. The analysis indicates that SiC and PyC exhibit the highest corrosion resistance, with nearly negligible corrosion rates owing to the formation of chemically inert passive layers. Meanwhile, ODS NiMo–Y₂O₃ demonstrates the best performance among metallic coatings due to the formation of a stable dual protective layer consisting of Cr₂O₃ and YOF. Although HEA provides relatively good corrosion resistance, its performance remains strongly dependent on the redox condition of the molten salt. Overall, the corrosion resistance ranking is determined as SiC ≈ PyC ODS NiMo–Y₂O₃ HEA Hastelloy-N. These findings provide a scientific basis for the development of hybrid coating materials with superior chemical stability and thermomechanical durability for structural applications in next-generation molten salt reactor systems.